1995
DOI: 10.1016/0005-2728(95)00015-b
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the mitochondrial three-subunit NADH dehydrogenase interaction with hexammineruthenium(III)

Abstract: The steady-state kinetics of the NADH dehydrogenase activity of the three-subunit flavo-iron-sulfur protein (FP, Type II NADH dehydrogenase) in the presence of the one-electron acceptor hexammineruthenium(III) (HAR) were studied. The maximal catalytic activities of FP with HAR as electron acceptor calculated on the basis of FMN content were found to be approximately the same for the submitochondrial particles, Complex I and purified FP. This result shows that the protein structure responsible for the primary N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 36 publications
4
21
0
Order By: Relevance
“…It has been shown previously that NADH-OH rapidly reacts with the oxidants ferricyanide and 2,6-dichlorophenolindophenol (26). Figure 2 shows that this is also true for HAR, the most efficient electron acceptor for complex I (21,22). Brief preincubation of NADH-OH with 0.5 mM HAR (the concentration used for the assay of the NADH dehydrogenase activity of complex I) completely abolished the inhibitory effect ( Figure 2, curves 1 and 2).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…It has been shown previously that NADH-OH rapidly reacts with the oxidants ferricyanide and 2,6-dichlorophenolindophenol (26). Figure 2 shows that this is also true for HAR, the most efficient electron acceptor for complex I (21,22). Brief preincubation of NADH-OH with 0.5 mM HAR (the concentration used for the assay of the NADH dehydrogenase activity of complex I) completely abolished the inhibitory effect ( Figure 2, curves 1 and 2).…”
Section: Resultsmentioning
confidence: 71%
“…For mechanistic models of the nucleotide substrate (product) interaction with the enzyme active site(s), only limited steadystate kinetic (18)(19)(20)(21)(22)(23)(24) and recent electrochemical (25) data are available. A very potent and specific inhibitor of the mitochondrial complex I, a derivative of NADH (tentatively identified as β-2,6-dihydroxydihydronicotinamide adenine dinucleotide), has been recently discovered (26).…”
mentioning
confidence: 99%
“…Among the representative membrane preparations listed in Table I, only the membranes from mutants E89C and E89A that were prepared in parallel batches exhibited a 45% higher activity. As the nonphysiological dNADH:HAR activity only depends on a functional 51-kDa subunit (31), this demonstrated that the complex I content of the membranes was not dramatically altered by the mutations. The observed differences in HAR activity were obviously because of variations in growth conditions and quality of the membranes.…”
Section: N-2 (30)mentioning
confidence: 78%
“…4C). Indeed, ROS production at the Q site should generate the formation of semiquinones (Ohnishi et al, 2010), while the FMN site involves a reduced, free Q4 flavin, a state favoured by high NADH to NAD+ ratio (Birrell and Hirst, 2013;Gavrikova et al, 1995;Kussmaul and Hirst, 2006). As DQ addition both increased the ratio of reduced (QH2) to oxidized quinone (Q) and reduces the ratio of NADH to NAD+, this should indicate the site involved in ROS formation between the FMN and quinone sites.…”
Section: The Fmn Site Is Responsible For the Production Of Rosmentioning
confidence: 96%
“…NADH Ubiquinone Reductase (NUR) activity was measured as described Medja et al, 2009). NADH dehydrogenase activity was measured by following the NADH oxidation at 340 nm with hexammineruthenium (HAR) as an electron acceptor (NADH:HAR activity) (Gavrikova et al, 1995). Assays were realized in a KH 2 PO 4 buffer (20 mM, pH 7.5) with 50 M NADH, 3.5 mM HAR, 4 g of solubilized OXPHOS proteins.…”
Section: Mitochondrial Respiration Rate and Enzymatic Measurementsmentioning
confidence: 99%